Influence of Progesterone Levels at AI and during Early Luteal Phase on Conception in Acyclic Sahiwal Cows Treated with Ovulation Synchronization Regimens - Paikra, Dilip Kumar; Awasthi, Manoj Kumar; Khan, Javed R; Parveen, Kaiser; Paikra, Dimpal; Sahu, Suryakant (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
The present experiment attempted to examine the influence of serum progesterone concentrations on conception rate in acyclic cows that were treated with three variants of ovsynch protocol. Postpartum (> 90 days) acyclic Sahiwal cows (n=18) were divided into three groups; each group consisted of six animals. Animals of group I were treated with modified ovsynch, group II animals with modified heat-synch and those of group III were treated with modified select-synch regimens. FTAI was performed in animals of group I and group II, whereas animals of group III were inseminated at detected estrus. Detection of conception was accomplished by ultrasonography on day 35 post-AI and confirmed later by examination per rectum between days 50-60 post-AI. Based on pregnancy diagnosis the animals were divided into conceived and non-conceived groups irrespective of treatment given to the animals. Blood samples were collected on the day of AI, days 10 and 20 post-AI for estimation of serum estradiol, insulin and progesterone levels using RIA kits. Results revealed that on the day of AI conceived animals had significantly higher serum estradiol concentrations (51.32±5.55 vs. 32.13±2.47 pg/mL, p ≤ 0.05) and insulin concentrations (17.61±0.74 vs. 12.94±0.39 µIU/mL, p<0.01) and lower serum progesterone levels (1.00±0.10 vs. 2.01±0.29 ng/mL, p ≤ 0.01) than in non-conceived animals. Conceived animals also recorded significantly higher (p ≤ 0.01) serum progesterone concentrations on day 10 (10.49±0.32 vs. 4.23±0.99 ng/mL) and day 20 (9.36±0.23 vs. 1.60±0.35 ng/mL) post-AI than in non-conceived animals. These observations highlighted two distinct prerequisites for successful conception; complete luteolysis before AI and strong luteal activity during early gestation